2010
DOI: 10.1530/eje-09-0875
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of thyroid dysfunction in human haematopoiesis: biochemical and molecular studies

Abstract: Objective: Abnormalities in haematological parameters have been noted in patients with thyroid diseases. Nevertheless, the exact mechanism of thyroid hormones' (THs) action on human haematopoiesis is still not entirely clear. Design: The influence of THs through TH receptors (TRa-1 and TRb-1) on haematopoiesis in patients with hypo-and hyperthyroidism was analysed. Methods: TR gene expression at the mRNA and protein levels in human CD34C -enriched haematopoietic progenitor cells (HPCs) obtained from the periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 29 publications
7
90
2
2
Order By: Relevance
“…Moreover, strong inhibition of terminal differentiation by T3 has been reported in Epo responsive NFS-60 cells [33] and we previously showed that T3 suppresses activin-induced K562 differentiation [19]. Hematopoietic progenitor cells obtained from hyperthyroid patients exhibit increased proliferative potential of BFU-Es and upregulation of cell cycle markers, compared to those from healthy volunteers [34]. These studies suggest that T3 exerts classical augmentation, but also has a suppressive effect on erythropoiesis, especially at a high concentration.…”
Section: Resultssupporting
confidence: 55%
“…Moreover, strong inhibition of terminal differentiation by T3 has been reported in Epo responsive NFS-60 cells [33] and we previously showed that T3 suppresses activin-induced K562 differentiation [19]. Hematopoietic progenitor cells obtained from hyperthyroid patients exhibit increased proliferative potential of BFU-Es and upregulation of cell cycle markers, compared to those from healthy volunteers [34]. These studies suggest that T3 exerts classical augmentation, but also has a suppressive effect on erythropoiesis, especially at a high concentration.…”
Section: Resultssupporting
confidence: 55%
“…These findings suggest that iatrogenic hypothyroidism has a negative effect on hematopoietic function, resulting in a reduction in red cell mass, and a concurrent negative effect on cardiovascular function, that together might increase morbidity (and thus perhaps mortality) in cats with iatrogenic hypothyroidism. Human patients with hypothyroidism are reported to have a macrocytic hypochromic anemia, which is associated with a reduced proliferative potential of hematopoietic stem cells 11. It is possible that a similar pathophysiologic mechanism could account for the reduced PCV that was observed in hypothyroid cats in the present study; however, further studies would be required to confirm this.…”
Section: Discussionsupporting
confidence: 52%
“…[22] Meanwhile, hypothyroidism will case anemia due to affect blood cells. [23] In this study, the levels of ferritin and HB were recorded to low in female patients with hypothyroidism as compared to healthy controls. These results are agreed with other studies which revealed that iron deficiency may be associated with low levels of thyroid hormones.…”
Section: Discussionmentioning
confidence: 81%